2016
DOI: 10.3389/fpls.2016.00138
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Reactive Oxygen Species Mediate Metabolic Changes in Barley Seed Embryo during Germination

Abstract: The levels of nitric oxide (NO) and reactive oxygen species (ROS), ATP/ADP ratios, reduction levels of ascorbate and glutathione, expression of the genes encoding proteins involved in metabolism of NO and activities of the enzymes involved in fermentation and in metabolism of NO and ROS were studied in the embryos of germinating seeds of two barley (Hordeum vulgare L.) cultivars differing in dormancy level. The level of NO production continuously increased after imbibition while the level of nitrosylated SH-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 61 publications
0
55
0
1
Order By: Relevance
“…Similarly to NO, ROS are known as key players to control seed dormancy and germination (Song et al , Ma et al ). Sarath et al () demonstrated the strong link between ROS, ABA and NO in grass seeds germination and these authors also found that DPI inhibits the seed germination, because it inhibits activity of the NADPH oxidase enzyme that produce ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to NO, ROS are known as key players to control seed dormancy and germination (Song et al , Ma et al ). Sarath et al () demonstrated the strong link between ROS, ABA and NO in grass seeds germination and these authors also found that DPI inhibits the seed germination, because it inhibits activity of the NADPH oxidase enzyme that produce ROS.…”
Section: Discussionmentioning
confidence: 99%
“…NO was highly abundant in nondormant genotypes and shared 69 loci with dormancy traits, indicative of a key role in dormancy alleviation. NO is generated from nitrate after imbibition by either nitrite reductase (Ma, Marsolais, Bykova, & Igamberdievi, 2016) or nonenzymatically in the aleuron cells (Bethke et al, 2007). NO is also stimulating both ethylene synthesis and signalling pathway (Arc, Sechet, Corbineau, Rajjou, & Marion-Poll, 2013).…”
Section: Marker-trait Associationsmentioning
confidence: 99%
“…Examining the kinetics of the production of reactive species, ROS formation occurs during imbibition, while the generation of NO is induced by oxygen depletion later, upon germination. The work of Ma et al (2016) gives a deeper insight into the metabolism of NO during seed germination. The germinating seed produces NO, which consequently leads to the intensification of thiol nitrosylation.…”
Section: Ros-no Interplay In Mature Seedsmentioning
confidence: 99%